The age, breed and sex pattern of diagnosis for veterinary care in insured cats in Japan. (February 2017) - Isomura, R.; Yamazaki, M.; Inoue, M.; Kwan, N. C. L.; Matsuda, M.; Sugiura, K.
Abstract : Objectives: To estimate the annual prevalence of different diagnostic categories by age, breed and sex in insured cats in Japan for which veterinary care claims had been made, and to identify if there is a pattern in these host factors. Materials and Methods: Data from 48, 187 cats insured for veterinary care in Japan in the period from April 2012 to March 2013 comprising 26, 003 males and 22, 184 females were analysed to calculate the annual prevalence of 18 diagnostic categories of disease by age, breed and sex. Results: The prevalence was highest for urinary system disorders (12·2% for males and 10·0% for females), followed by digestive disorders (11·6% for males and 10·7% for females) and dermatological diseases (8·7% for males and 9·0% for females). The male cats had a higher prevalence than female cats for most diagnostic categories. The prevalence of cardiovascular, urinary, endocrine and neoplastic disorders increased with age; infectious and parasitic diseases had high prevalence at young ages, and the prevalence of respiratory, musculoskeletal disorders and injuries had bimodal peaks. Dermatological disorders had a high prevalence at all ages. A large variation in prevalence was observed between breeds for otic, dermatological, dental and cardiovascular disorders. Clinical Significance: The findings can be used to increase awareness of patterns of health disorders in different categories of cat.